Pelatihan dan Pemagangan serta Peluang Kerja Pemuda di Indonesia: Analisis Data Sakernas 2022 - Ulhaq, Muhammad Dhiya (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
Fluctuations in Indonesia’s economic growth have affected labor absorption amid an increasing labor force and a declining unemployment rate in 2022. Nevertheless, low labor competitiveness and skill mismatches with labor market demand remain major challenges, particularly for young people. This study aims to analyze the impact of training and apprenticeship on employment probability in Indonesia while accounting for potential selection bias in participation in skill-development programs. The study utilizes data from the August 2022 National Labor Force Survey (Sakernas), comprising 752,688 observations. The analytical method employed is Propensity Score Matching (PSM) to estimate the Average Treatment Effect on the Treated (ATT), with employment status as the outcome variable and covariates including educational attainment, age, gender, area of residence, marital status, and school enrollment status. The estimation results indicate that participation in training has a positive and statistically significant effect on employment probability, increasing the likelihood of being employed by approximately 13–14 percentage points for training participants after matching. In addition, apprenticeship participation also exhibits a positive and significant impact on employment status, increasing employment probability by approximately 11 percentage points after controlling for observable individual characteristics. These findings suggest that both training and apprenticeship play an important role in improving employment opportunities, albeit through different mechanisms. Both indicate that skills development programmers can be an effective labour market policy instrument for improving youth transition to employment.